[OP.1C.09] VARIABILITY OF 24 HOUR BLOOD PRESSURE: AN INDEPENDENT DETERMINANT OF ARTERIAL STIFFNESS. (September 2017) - Antza, C.; Doundoulakis, I.; Stabouli, S.; Kotsis, V.
Abstract : Objective: The aim of the study was to identify if arterial stiffness is influenced by the variability of 24 hour blood pressure. Design and method: 365 consecutive subjects (50.9% male) aged 47.51 ± 22.81 years were included in the study. Subjects were never treated before for hypertension. All subjects underwent 24 h-ABPM on a usual working day. Pulse wave velocity (PWV) was measured after 15 minutes of rest in the supine position. The subject was not speaking or sleeping in a quiet, semi-darkened, temperature-controlled laboratory. Participants had been advised to refrain from eating, smoking and drinking caffeine beverages and alcohol before measurement. PWV was calculated as the transit time of the arterial pulse along the carotid-femoral distance divided with the distance measured directly and modified according the guidelines. Results: The 24 h variability of systolic BP (24 h SD-SBP) was found 14.19 ± 3.76 mmHg, the 24 h variability of diastolic BP (24 h SD-DBP) was found 10.94 ± 2.30 mmHg and the 24 h variability of heart rate (24 h SD-HR) was found 10.26 ± 3.70. Carotid-femoral PWV was 8.98 ± 3.31m/sec. In the univariate analysis, carotid-femoral PWV was correlated with age, gender, hip measurement, 24 h average of SBP, 24 h average of DBP, LDL levels, e-GFR, 24 h SD-SBP, 24 h SD-DBP and 24 h SD-HR (p < 0.05 for all). However, in the multiple linear regression model, only age, e-GFR, 24 h average of SBP, 24 h average of DBP, 24 h SD-SBP and 24 h SD-DBP (p < 0.05 for all) remained significant predictors of carotid-femoral PWV, even after adjustment for other factors. Conclusions: The variability of systolic and diastolic 24 h blood pressure is an independent predictor of arterial stiffness, suggesting a role for increased variability in the pathophysiology of large arteries arteriosclerosis independent of age, gender, hip measurement, LDL levels, blood pressure levels recorded with the 24h-ABPM and kidney function.